The Relationship Of Breastfeeding Mother's Behavior And Exclusive Asi Feeding In Pasar Gambir Health Center, Tebing Tinggi City, 2022 - Hayati , Nila (Sean Institute, 2023)
Breast milk is a food that contains a complete nutritional composition that is needed for growth and development for babies. Exclusive breastfeeding is not achieved according to the target. Exclusive breastfeeding is influenced by the behavior of breastfeeding mothers. This study aims to determine the relationship between breastfeeding mother's behavior and exclusive breastfeeding at Pasar Gambir Health Center, Tebing Tinggi City in 2022. This research is a quantitative research with a cross sectional approach. This research was conducted from September 26, 2022 to October 8, 2022. Sampling used purposive sampling with a total sample of 32 people. The results showed that the majority of breastfeeding mothers' knowledge in providing exclusive breastfeeding at Pasar Gambir Health Center, Tebing Tinggi City in 2022 was sufficient, the attitude of breastfeeding mothers in providing exclusive breastfeeding at Pasar Gambir Public Health Center, Tebing Tinggi City in 2022 was mostly positive and the actions of breastfeeding mothers in providing breast milk. Exclusively at Pasar Gambir Health Center, Tebing Tinggi City in 2022, the majority is sufficient. Based on the results of the chi-square test, it was found that knowledge (0.001 <0.05), attitude (0.001 <0.05) and action (0.001 <0.05). So it can be concluded that there is a relationship between the behavior of breastfeeding mothers and exclusive breastfeeding at the Pasar Gambir Health Center, Tebing Tinggi City in 2022. Suggestions in this study are Pasar Gambir Health Center in Tebing Tinggi City to provide continuous education about exclusive breastfeeding by increasing the knowledge, attitudes and actions of mothers in order to optimize the achievement of exclusive breastfeeding.